Variations in the diagnostic performance of transurethral resection of bladder tumor with photodynamic diagnosis according to surgical experience: A retrospective, single-center study - Shuhei Suzuki; Yoshiyuki Nagumo; Kosuke Kojo; Atsushi Ikeda; Bunpei Isoda; Akane Yamaguchi; Kozaburo Tanuma; Satoshi Nitta; Masanobu Shiga; Takashi Kawahara; Shuya Kandori; Akio Hoshi; et al. (Photodiagnosis and Photodynamic Therapy)
Background: To investigate variations in diagnostic performance of photodynamic diagnosis (PDD) according to surgical experience. Methods: Data were extracted from patients having pT1 or lower primary tumors that underwent PDD-assisted transurethral resection of bladder tumors (TURBT) with orally 5-amibolevulinic acid at our institute. Surgical experience was categorized by urological experience (first-year and second-year) and PDD experience (<10, 10–19, and ≥20 cases). Sensitivity, specificity, and accuracy rates were calculated based on PDD or white light (WL) findings and pathologic diagnosis. The bladder neck, trigone, and prostatic urethra were defined as areas with a high probability of tangential effect. Results: A total of 108 patients and 343 specimens were extracted. The second-year surgeons had significantly higher accuracy rates than first-year surgeons (81.5 % vs. 69.0 %, p = 0.013), while PDD experience did not significantly affect accuracy rates (76.5, 75.5, and 69.0 %). In addition, the accuracy rate was also significantly lower in tangential effect areas (59.6 % vs. 80.8 %). Multivariate analysis identified urological experience as a significant factor improving accuracy rate (odds ratio [OR] 2.14) while tangential effects substantially reduced accuracy rate (OR 0.37). Notably, combining both PDD and WL resulted in a sensitivity exceeding 94 %, even in first-year urology residents and tangential effect areas. Conclusions: Urological experience had a greater impact on diagnostic performance of PDD compared to PDD experience. The combination of PDD and WL findings may improve sensitivity and reduce the possibility of missed diagnoses for less experienced urology residents.